Website design and development with HTML5 and CSS3 - Rebah, Hassen Ben; Boukthir, Hafedh; Chedebois, Antoine (John Wiley & Sons, Inc., 2021)
Combining theory and practice, Website Design and Development with HTML5 and CSS3 is aimed at both beginners who want to design their first website, and experienced developers who want to consolidate their technical skills. This book addresses the theoretical aspects of HTML5 and CSS3, including: HTML elements, semantic containers, semantic text formatting, multimedia elements, forms, tables, definition and integration of CSS styles, text formatting, and container and box styles. It also encompasses a practical section which presents the process of creating a website, as well as the key rules to apply in order to not only achieve project success, but also to meet user needs. Illustrated by numerous examples, this book includes corrected practical work, structured according to an evolutionary logic ranging from the design of a simple HTML5 page to the creation of a professional website.